Managing people in the hospitality industry - Riley, Michael (Abingdon, Oxon ; New York, NY Routledge, 2019)
This is a book about being a successful manager in the complex hospitality industry. Approaching the subject in the context of personal development, it offers future managers essential knowledge and insight into the opportunities, the constraints, the problems and the solutions that face management at any level in the industry. Structured in six parts, this comprehensive volume is not merely concerned with the social and psychological aspects of people management, but also with the economics of labour, including: labour costs, utilisation, labour market behaviour and pay. These aspects are conjoined in the book with the skills of people management to reflect the dynamics of real-life practice. Combining theory and practice, Managing People in the Hospitality Industry offers a concise portrait of the industry at work and is essential reading for the hospitality managers of tomorrow. --
Prof. Leahlizbeth Sia (Recommending faculty) - Bookfair 2019
Includes bibliographical references and index.
Keywords: Hospitality industry -- Personnel management; Tourism -- Personnel management